Cellular vaccines in listeriosis: role of the Listeria antigen GAPDH - Calderon-Gonzalez, Ricardo; Frande-Cabanes, Elisabet; Bronchalo-Vicente, Lucia; Lecea-Cuello, M.Jesus; Pareja, Eduardo; Bosch-Martinez, Alexandre; L.Fanarraga, Monica; Yañez-Diaz, Sonsoles; Carrasco-Marin, Eugenio; Alvarez-Dominguez, Carmen (Frontiers in Cellular and Infection Microbiology, 2014)
The use of live Listeria-based vaccines carries serious difficulties when administrated to immunocompromised individuals. However, cellular carriers have the advantage of inducing multivalent innate immunity as well as cell-mediated immune responses, constituting novel and secure vaccine strategies in listeriosis. Here, we compare the protective efficacy of dendritic cells (DCs) and macrophages and their safety. We examined the immune response of these vaccine vectors using two Listeria antigens, listeriolysin O (LLO) and glyceraldehyde-3-phosphate-dehydrogenase (GAPDH), and several epitopes such as the LLO peptides, LLO189–201 and LLO91–99 and the GAPDH peptide, GAPDH1–22. We discarded macrophages as safe vaccine vectors because they show anti-Listeria protection but also high cytotoxicity. DCs loaded with GAPDH1–22 peptide conferred higher protection and security against listeriosis than the widely explored LLO91–99 peptide. Anti-Listeria protection was related to the changes in DC maturation caused by these epitopes, with high production of interleukin-12 as well as significant levels of other Th1 cytokines such as monocyte chemotactic protein-1, tumor necrosis factor-α, and interferon-γ, and with the induction of GAPDH1–22-specific CD4+ and CD8+ immune responses. This is believed to be the first study to explore the use of a novel GAPDH antigen as a potential DC-based vaccine candidate for listeriosis, whose efficiency appears to highlight the relevance of vaccine designs containing multiple CD4+ and CD8+ epitopes.